Stages d'enseignement dans les commissions scolaires anglophones du Québec - Pattison-Meek, Joanne; Henderson-Croteau, Ashley (Quebec English-speaking Communities Research Network (QUESCREN), 2025)
Chaque année, le gouvernement provincial finance des expériences de formation supervisées en milieu scolaire pour les stagiaires en enseignement, appelées « stages d’enseignement ». Le présent résumé examine la répartition de ces fonds entre les neuf commissions scolaires anglophones en fonction de la proportion de stagiaires en enseignement qu’elles accueillent en provenance des universités québécoises. Les données mettent en évidence une concentration des stages d’enseignement dans les commissions scolaires situées à proximité des universités anglophones et dans le grand Montréal, ce qui désavantage certaines écoles en régions rurales et éloignées.

Student Teacher Practicums in English School Boards in Quebec - Pattison-Meek, Joanne; Henderson-Croteau, Ashley (Quebec English-speaking Communities Research Network (QUESCREN), 2025)
Each academic year the provincial government provides financial support for supervised, in-school training experiences for student teachers, known as teaching practicums. This brief examines how these funds are distributed across the nine English school boards based on the proportion of student teachers they host from Quebec universities. The data highlights a concentration of teaching practicums undertaken in school boards with proximity to English universities and Greater Montreal, thereby disadvantaging some rural and remote schools.

Inclusion des Québécois d’expression anglaise au Programme d’accès à l’égalité en emploi - Bourhis, Richard Y. (Quebec English-speaking Communities Research Network (QUESCREN), 2025)
Le Programme d’accès à l’égalité en emploi (PAÉE) du gouvernement du Québec cible cinq groupes vulnérables sous-représentés dans l’administration publique. La minorité anglophone ne fait pas actuellement partie de ces groupes. Toutefois, depuis plusieurs décennies, les anglophones ont connu un déclin de leur vitalité institutionnelle et économique, malgré des niveaux élevés d’accomplissement scolaire et un bilinguisme croissant. En comparaison avec les francophones, les anglophones se trouvent maintenant dans des conditions socio-économiques moins favorables, avec des salaires médians annuels inférieurs, ainsi que des taux de chômage et de pauvreté plus élevés dans la plupart des 17 régions administratives du Québec. De plus, ils déclarent subir davantage de discrimination et de linguicisme que la majorité francophone. Leur participation dans la fonction publique québécoise reste très faible (1 %) par rapport à leur proportion de 10% dans la population provinciale selon la langue maternelle. Compte tenu de ces éléments, il est recommandé d’envisager l’inclusion des Québécois d’expression anglaise comme groupe cible du PAÉE. Ce document de travail porte sur le PAÉE que la Commission des droits de la personne et des droits de la jeunesse (CDPDJ) administre pour 338 organismes publics.

Inclusion of English-speaking Quebecers in the Equal Access Employment Program - Bourhis, Richard Y. (Quebec English-speaking Communities Research Network (QUESCREN), 2025)
The Quebec government’s Equal Access Employment Program (EAEP) targets five vulnerable, underrepresented groups in the public service. The anglophone minority is not currently one of them. However, in the past few decades, anglophones have experienced a decline in their institutional and economic vitality despite high levels of academic achievement and growing bilingualism. Compared with francophones, anglophones now live in less favourable socioeconomic conditions, with lower annual median incomes and higher unemployment and poverty rates in most of the 17 administrative regions of Quebec. They also report higher levels of discrimination and linguicism than the francophone majority. Their participation in Quebec’s public service remains very low (1%) when one considers that mother tongue anglophones make up 10% of the provincial population. In light of the above, we recommend considering including English-speaking Quebecers as an EAEP target group. This paper focuses on the EAEP that the Commission des droits de la personne et des droits de la jeunesse (CDPDJ) administers for 338 public organizations.

Proposal for Including English-speaking Quebecers in the Programme d'accès a l'égalité en emploi (PAÉE) - Bourhis, Richard Y. (2024)

Disparités de revenus entre les anglophones et les francophones du Québec au fil du temps - Donovan, Patrick; Bell, Shannon (Quebec English-Speaking Communities Research Network (QUESCREN), 2024)
Le présent rapport aborde les disparités de revenus entre les anglophones et les francophones du Québec. On y examine les changements survenus depuis le début du 20e siècle, époque où les anglophones dominaient dans de nombreuses industries clés, ainsi que les changements politiques et culturels survenus entre 1940 et 1980, jusqu’au contexte actuel.

Income Disparities Between Quebec's English Speakers and Francophones Over Time - Donovan, Patrick; Bell, Shannon (Quebec English-Speaking Communities Research Network (QUESCREN), 2024)
This brief looks at income disparities between English speakers and Francophones in Quebec. It examines changes from the early 20th century, when Anglophones dominated many major industries, through political and cultural shifts between 1940 and 1980 to today’s landscape.

Financement des universités francophones et anglophones du Québec : S'agit-il vraiment d'un jeu à somme nulle ? : Résumé de recherche no. 11 - Bell, Shannon; Donovan, Patrick (Quebec English-speaking Communities Research Network (QUESCREN), 2024)

French and English Universities in Quebec : Is It Really a Zero-Sum Game? : Research Brief no. 11 - Bell, Shannon; Donovan, Patrick (Quebec English-speaking Communities Research Network (QUESCREN), 2024)

Exploring the English-speaking Landscape : A Typology of Vulnerability Associated with Employment in Quebec's English-speaking Population - Warnke, Jan; Bolger, Laura-Lee (Quebec English-Speaking Communities Research Network (QUESCREN), 2024)
This exploratory study uses geodemographic analytical methods to investigate the English-speaking population of Quebec, with a specific focus on vulnerability indicators associated with employment and their spatial distribution within the province. Using Ward’s cluster analysis method, eight distinct groups were identified and mapped, each showcasing unique characteristics that warrant tailored policy measures to effectively tackle regional employment challenges. Future research should delve into the differential impacts of various variables across clusters, particularly those related to mobility and aboriginal identity, thereby facilitating the derivation of targeted policy interventions.

Avoiding the News Desert : Addressing Challenges Around Community Media in English-speaking Quebec : Research Brief no. 10 - Bell, Shannon (Quebec English-speaking Communities Research Network (QUESCREN), 2023)

Éviter le désert mediatique : Relever les défis des médias régionaux dans le Québec anglophone : Résumé de recherche no. 10 - Bell, Shannon (Quebec English-speaking Communities Research Network (QUESCREN), 2023)

They “Could Care for Our Elderly in Our Homes” : The Historical Impact of Black Caregivers - Williams, Dorothy W. (2023)
My aim is to interrogate prevalent assumptions about health and social services through a survey of notable chapters in the history of Black caregiving in Quebec. The assumptions have created expectations and a false narrative built upon historical myths and erasures that undergird the provincial population’s understanding of its relationship with Black caregivers. Blacks, both Francophone and Anglophone, though not exclusively so, have had significant connection to the care and well-being of Quebec’s residents. Black caregiving in Quebec is not recent—indeed, Black caregivers have been intimately tied to Quebec’s labour force aspirations and development for centuries. Even so, it is rarely acknowledged, to the point of being virtually unknown. This paper seeks to address those gaps in the narrative by presenting a timeline dating back to the 17th century. It will reveal intricate connections between the different periods when it comes to segregation, prejudice, migration, immigration quotas, and bans.
Parallel title: QUESCREN Working Paper no. 10

Brief to the House of Commons Standing Committee on Official Languages on the Topic of Bill C-13, an Act To Amend the Official Languages Act, to Enact the Use of French in Federally Regulated Private Businesses and to Make Related Amendments to Other Acts - O'Donnell, Lorraine (Quebec English-speaking Communities Research Network (QUESCREN), 2022)
The present brief focuses on the first purpose, Bill C-13 amendments to the OLA. This is the topic on which I in my role as research associate at the Quebec English-Speaking Communities Research Network (QUESCREN) have developed the most knowledge.
Parallel title: BRIEF To the House of Commons Standing Committee on Official Languages

Mémoire présenté au Comité permanent des langues officielles de la Chambre des communes au sujet du projet de loi C-13 : Loi modifiant la Loi sur les langues officielles, édictant la Loi sur l’usage du français au sein des entreprises privées de compétence fédérale et apportant des modifications connexes à d’autres lois - O'Donnell, Lorraine (Quebec English-speaking Communities Research Network (QUESCREN), 2022)
Le présent mémoire est axé sur le premier objectif — les modifications apportées à la LLO par le projet de loi C-13 —, car il s’agit du sujet sur lequel j’ai développé le plus de connaissances à titre d’attachée de recherche pour le Réseau de recherche sur les communautés québécoises d’expression anglaise (QUESCREN)
Parallel title: MÉMOIRE présenté au Comité permanent des langues officielles de la Chambre des communes

The Tourist Offer of the Whiteley Museum and its Surrounding Area on the Lower North Shore : A Quality Improvement Report - Donovan, Patrick; O'Donnell, Lorraine (Quebec English-speaking Communities Research Network (QUESCREN), 2022)
This report analyzes the tourist offer in the eastern part of Quebec’s Lower North Shore, particularly the municipality of Bonne-Espérance, a region where English speakers make up the majority of the population. It focuses specifically on an institution in one of these municipalities, the Whiteley Museum. The report provides the authors’ suggestions to improve tourism development as a means to diversify the economy, potentially help reverse demographic decline, and build community vitality.

Comparing Unemployment Rates Among Québec's English and French Speakers by Education Level - Dufour, Caroline (2021)

Forum for Youth Insights : Career and Education Orientations for the Post-COVID-19 World - Cohen, Eric (Quebec English-speaking Communities Research Network (QUESCREN), 2020)
The kids are (mostly) alright! That message was made loud and clear during a fascinating discussion when a group of passionate thinkers, educators, students, and speakers got together virtually on October 25, 2020, for Concordia University’s Forum for Youth Insights. An initiative of the Quebec English-Speaking Communities Research Network through its Inter-Level Educational Table, in collaboration with Youth 4 Youth Québec and the Black Community Resource Centre, this year’s forum had a special theme : Career and Education Orientations for the Post-COVID-19 World. In a nutshell, it was an opportunity for students to understand the new realities of the post-COVID-19 experience and how to navigate the sometimes confusing road ahead. Spoiler alert : We’re gonna be alright (but we need to recalibrate slightly).
Parallel title: Report : Key Insights and Takeaways

Forum sur les perspectives jeunesse : orientations professionnelles et éducatives dans le monde post-COVID-19 - Cohen, Eric (Quebec English-speaking Communities Research Network (QUESCREN), 2020)
La jeunesse va (globalement) bien ! Ce message a été exprimé haut et fort lors d’une discussion captivante entre intellectuels, éducateurs, étudiants et conférenciers passionnés, qui s’est tenue virtuellement le 25 octobre 2020 dans le cadre du Forum sur les perspectives jeunesse de l’Université Concordia. L’événement a eu lieu à l’initiative du Réseau de recherche sur les communautés québécoises d’expression anglaise, par l’entremise de sa Table d’éducation interordres et en collaboration avec Youth 4 Youth Québec et le Centre de ressources de la communauté noire. Cette année, le forum avait un thème bien particulier : Orientations professionnelles et éducatives dans le monde post-COVID-19. En résumé, l’occasion a été donnée aux étudiants de saisir les nou- velles réalités de ce « monde d’après » afin qu’ils sachent comment s’engager sur la voie parfois déconcertante qui s’ouvre à eux. Alerte au divulgâcheur : tout va bien aller (mais il nous faudra procéder à quelques ajustements).
Parallel title: Rapport sue les idées et enseignements du forum

Employment of English Speakers in Quebec's Public Service - Cooper, Celine; Donovan, Patrick; O'Donnell, Lorraine (Quebec English-speaking Communities Research Network (QUESCREN), 2019)
This document provides background information related to the participation of English speakers in Quebec’s Public Service (QPS). The first section synthesizes information from relevant primary and secondary sources. The second section includes summaries of preliminary discussions with key informants, as well as our observations.
Parallel title: QUESCREN Working Paper no.1
Keywords: Official Language Minority Community (OLMC)

Les Québécois d'expression anglaise et la fonction publique du Québec - Cooper, Celine; Donovan, Patrick; O'Donnell, Lorraine (Quebec English-speaking Communities Research Network (QUESCREN), 2019)
Ce document de travail fournit des renseignements contextuels sur la participation des anglophones à la fonction publique du Québec (FPQ). La première partie fait la synthèse de l’information pertinente recueillie auprès de sources primaires et secondaires. La seconde offre un résumé de nos discussions exploratoires avec des personnes-ressources clés, suivi de nos observations.
Parallel title: Document de travail QUESCREN no.1
Keywords: Official Language Minority Community (OLMC)

QCGN/Community Pleased with Funding from Secretariat - Quebec Community Groups Network (QCGN) (2018)

L'économie créative et les communautés anglophones au Québec: Rapport préparé pour Industrie Canada par Tracy Zhang - Zhang, Tracy (Quebec English-speaking Communities Research Network (QUESCREN), 2012)
L’économie créative et les communautés anglophones au Québec présente les résultats préliminaires d’une étude comprenant un groupe de discussion, des entrevues privées avec des intervenants clés et des recherches documentaires. Le rapport démontre que l’idée d’économie créative est utile au suivi du développement culturel et économique des communautés anglophones du Québec (CAQ). Les anglophones québécois constituent la plus importante communauté minoritaire de langue officielle provinciale au Canada. Au cours des dernières décennies, la composition de cette population est devenue de plus en plus complexe et multiculturelle. Parallèlement à ces changements démographiques, l’influence de la culture anglophone québécoise a aussi évolué. On dit qu’une proportion particulièrement élevée d’anglophones est engagée dans le secteur des arts, de la culture et du patrimoine. Dans ce contexte, les organismes du secteur jouent un rôle croissant dans le développement socioéconomique des CAQ. Le présent rapport révèle les préoccupations grandissantes des représentants de certains organismes de ce type qui ont participé à l’étude en ce qui a trait à la manière d’appliquer la théorie de l’économie créative de façon à créer des modèles de développement culturel et économique efficaces pour les CAQ.
Keywords: Official Language Minority Community (OLMC)

The Creative Economy and the English Speaking Communities in Quebec : Report Submitted to Industry Canada by Tracy Zhang on Behalf of the Quebec English-speaking Communities Research Network (QUESCREN) - Zhang, Tracy (Quebec English-speaking Communities Research Network (QUESCREN), 2012)
The Creative Economy and English-Speaking Communities in Quebec presents preliminary research results based on a focus group, private key informant interviews, and bibliographical research. It demonstrates that the concepts of the creative economy are useful in charting cultural and economic development for the English-speaking communities in Quebec (ESCQ). The English-speaking population in Quebec forms the largest provincial Official Language Minority Community in Canada. In recent decades, the composition of this population has become increasingly complex and multicultural. Parallel to this demographic shift, the influence of English-language Quebec culture has also evolved. English-speakers are said to have a high participation rate in the arts, culture and heritage sectors. In this context, organizations from these sectors are increasingly involved in supporting the socioeconomic development of the ESCQ. This report reflects growing concerns on the part of representatives of some of these organizations who participated in the study over how to apply the creative economy theory to generate effective models of cultural-economic development for the ESCQ.
Keywords: Official Language Minority Community (OLMC)